Screening stringency in the disability insurance program - Per Johansson; Lisa Laun; Tobias Laun (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2013)
We propose a strategy for assessing how the inflow to the disability insurance program has been governed over time. We analyze the ex-ante health of individuals entering the program, compared to individuals not entering the program in the same year, by using ex-post mortality. Applying the strategy to Sweden, we find large variation in the relative health of new beneficiaries compared to non-beneficiaries over time. Some of the fluctuations correspond well to formal changes to screening stringency. However, we also find large variation in health during periods when no changes to formal eligibility criteria have been pursued.
Keywords: C41; I18; J14; 330; disability insurance; screening stringency; proportional hazard model; Erwerbsunfähigkeitsrente; Gesundheit; Statistische Bestandsanalyse; Schweden